1967
DOI: 10.2136/sssaj1967.03615995003100040030x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Pan Characterization of Selected Coastal Plain Soils

Abstract: Tillage pan characteristics in Lakeland, Norfolk, Red Bay and Orangeburg soil series were studied at 20 paired locations of cultivated and virgin areas. Pits for sampling were dug following periods of heavy rainfall. Tillage pans were identified by pocket penetrometer readings of the compaction. Sampling depths from adjacent virgin sites corresponded to those in the cultivated sites. These pans showed consistently higher compaction, bulk density, and less pore space than the soil above or below the pan or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Nutrient recycling, however, resulted in excessive nutrient availability which resulted in excess growth that reduced cotton yield. A zone of soil compaction spans most of the soils at the 15 to 30 cm soil depth in the SE (Kashirad et al, 1967;Campbell et al, 1974). Bahiagrass develops a deep and extensive root system that can penetrate through this zone of compaction (Elkins et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient recycling, however, resulted in excessive nutrient availability which resulted in excess growth that reduced cotton yield. A zone of soil compaction spans most of the soils at the 15 to 30 cm soil depth in the SE (Kashirad et al, 1967;Campbell et al, 1974). Bahiagrass develops a deep and extensive root system that can penetrate through this zone of compaction (Elkins et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless several studies have shown that many chemical and physical soil properties change on much shorter time scales (Anderson and Browning 1949;van Bavel and Schaller 1950;Kashirad et al 1967;Barnes et al 1971;Bouma and Hole 1971;Davies et al 1972;Skidmore et al 1975;Greenland 1977;Meints and Peterson 1977;Van Cleve and Moore 1978;Pidgeon and Soane 1978;Martel and Mackenzie 1980;Coote and Ramsey 1983;Mann 1985Mann , 1986Johnston 1986;Jenkinson 1991;Sandor and Eash 1991;Bouman et al 1995;Barak et al 1997;Khan et al 2007;David et al 2009;Mulvaney et al 2009). These changes are assumed to be inconsequential to the fundamental character of the soil given none of the authors recommended reclassifying their study soils.…”
mentioning
confidence: 99%
“…oil compaction is an acute problem in the southeastern U.S., with hardpan profiles restricting root growth (Kashirad et al, 1967;Cooper et al, 1969;Reicosky et al, 1977). Roots are unable to grow during short-term drought conditions, which are frequently present during the growing season.…”
mentioning
confidence: 99%